2002
DOI: 10.1007/3-540-45664-3_14
|View full text |Cite
|
Sign up to set email alerts
|

On the Security of the Threshold Scheme Based on the Chinese Remainder Theorem

Abstract: Threshold schemes enable a group of users to share a secret by providing each user with a share. The scheme has a threshold t + 1 if any subset with cardinality t + 1 of the shares enables the secret to be recovered. In 1983, C. Asmuth and J. Bloom proposed such a scheme based on the Chinese remainder theorem. They derived a complex relation between the parameters of the scheme in order to satisfy some notion of security. However, at that time, the concept of security in cryptography had not yet been formalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 9 publications
1
42
0
1
Order By: Relevance
“…We will use the following definition of a threshold secret-sharing scheme, which is a slight modification of the definition in [17].…”
Section: Definition Of Changeable-threshold Secret-sharing Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…We will use the following definition of a threshold secret-sharing scheme, which is a slight modification of the definition in [17].…”
Section: Definition Of Changeable-threshold Secret-sharing Schemesmentioning
confidence: 99%
“…The correctness and security properties of a (t, n)-threshold secret-sharing scheme can be quantified by the following definitions, which are modifications of those in [17].…”
Section: Definition Of Changeable-threshold Secret-sharing Schemesmentioning
confidence: 99%
“…Let S be the adversarial coalition of size t − 1, and let y be the unique solution for y in Z M S . According to (1), Quisquater et al [14] showed that when moduli m i are chosen as consecutive primes 1 ≤ i ≤ n, the scheme has better security properties. In this paper, we assume that all m i are selected as consecutive primes.…”
Section: The Asmuth-bloom Secret Sharing Schemementioning
confidence: 99%
“…However, this scheme is not exactly perfect since when t À 1 shares are known, the key candidates are not equally likely as described in Section 4. We refer the reader to a recent work by Quisquater et al [22] for a detailed security analysis of Asmuth-Bloom and some other Chinese Remainder Based SSSs.…”
Section: Asmuth-bloom Secret Sharing Schemementioning
confidence: 99%